Correlation between appearance of the retroportal fat plane at preoperative CT and pathology findings in resected adenocarcinoma of the pancreatic head. Issue 4 (April 2019) - Lombardo, F.; Zamboni, G.A.; Bonatti, M.; Chincarini, M.; Ambrosetti, M.C.; Marchegiani, G.; Malleo, G.; Mansueto, G.; Pozzi Mucelli, R.
Abstract : AIM: To correlate the appearance of the retroportal fat plane at preoperative computed tomography (CT) and the pathology findings in resected adenocarcinoma of the pancreatic head (PDAC). MATERIAL AND METHODS: Forty-eight patients with resected PDAC of the pancreatic head were included (24 men, 24 women, mean age 63 years, median BMI 24.1). All patients underwent CT <30 days before surgery. The state of the retroperitoneal resection margin and the presence of lymphatic or perineural invasion were obtained from pathology reports. CT images were reviewed independently by two radiologists for assessment of the retroportal fat plane and graded in two categories (clear/effaced). Inter-reader discrepancies were solved in consensus. Interobserver agreement was calculated and Fisher's test was used to assess the correlation between CT and pathology findings. Visceral fat areas were measured and correlated with CT findings. RESULTS: A clear retroportal fat plane was significantly associated with a negative retroperitoneal margin at pathology with 100% specificity and PPV ( p= 0.0001). No association was observed between the appearance of the fat plane at CT and the presence of lymphatic or perineural invasion ( p= ns). Interobserver agreement for retroportal fat plane evaluation was good (0.741). False-positive cases had a significantly lower visceral fat area than the correctly classified patients ( p= 0.0480). CONCLUSIONS: A clear retroportal fat plane is significantly associated with negative retroperitoneal resection margins at pathology. The lack of visceral adipose tissue can lead to overestimation of retroportal fat plane involvement at preoperative CT. Highlights: A clear retroportal fat plane at CT is associated with R0 margin at pathology. Neo-adjuvant chemotherapy is associated with a high number of false positives. Lack of visceral adipose tissue can lead to false positive results.